Effect of Mirror Therapy on mu rhythm of Electroencephalogram Signals - Xuefeng LIU; Weilin LIU; Qiurong XIE; Jian HE (康复学报)
Objective:To observe the changes of mu rhythm of electroencephalogram (EEG) signals in healthy human beings received mirror therapy under the conditions of movement imagination, passive movement and movement execution.Methods:Fourteen subjects of healthy adults from Fujian University of Traditional Chinese Medicine were recruited in the present study. Every subject received mirror therapy under the conditions of movement imagination, passive movement and active movement respectively. The mu rhythm of EEG signals was analyzed and contrasted under conditions of movement imagination, passive movement and active movement during mirror therapy as well as quiescent conditions using Neuroscan4.5 System.Results:The phenomenon of mu suppression was mainly observed at electrodes of CZ, CPZ, P3 and C3 while subjects were performing movement imagination, active movement and passive movement. The phenomenon of mu suppression was more obvious at electrodes of CZ, P3 and C3 while subjects were performing active movement and movement imagination compared with passive movement (P<0.05).Conclusion:Significant changes of mu rhythm that produces the phenomenon of mu suppression can be found while performing mirror therapy in healthy human beings, and mirror therapy under the conditions of movement imagination and active movement plays important roles on mu rhythm changes and mu suppression.